THE HARMONY OF TOLERANCE IN THE UPBRINGING AND FORMATION OF A MATURE GENERATION - Saparov Murod Yuldashovich (Western European Studies, 2025)
To form a harmonious generation, it is necessary to correctly explain the essence of secularism in our state's policy in the cognitive development of tolerance in the personality and thinking of young people.
Keywords: Youth; high intellectual; spiritual competence